Immunologic Evaluation of Patients with Cefotetan-Induced Anaphylaxis - Nam, Young-Hee (Allergy Asthma Immunol Res, 2015)
Cefotetan is a commonly prescribed second-generation cephalosporin that acts against a wide range of bacteria. However, cefotetan-induced hypersensitivity has rarely been reported. We report 2 cases of cefotetan-induced anaphylaxis with immunologic evaluation. The first case was a 70-year-old asthmatic woman who had dyspnea and hypotension during administration of cefotetan, in which high serum-specific IgE to cefotetan-human serum albumin (HSA) conjugate was detected by enzyme-linked immunosorbent assay. The second case was a 63-year-old asthmatic woman who complained of chest tightness and dyspnea during cefotetan infusion, in which high serum-specific IgG1 and IgG4 with no serum specific IgE to cefotetan-HSA conjugate was detected. The basophil activation test using basophils from the patient showed a significant up-regulation of CD63 with the addition of anti-IgG4 antibody compared with that in non-atopic healthy controls. In conclusion, cefotetan can induce anaphylaxis, which may involve both IgE- and IgG4-mediated responses in the pathogenic mechanism.